P-007 Trends in aneurysm treatment modality at a single, high-volume tertiary care center. (12th July 2011) - Spiotta, A; Wheeler, A; Hui, F; Rasmussen, P; Moskowitz, S
Abstract : Introduction: Device developments and evolution in technique over the past decade since the International Study of Aneurysms Trial results were first available make the treatment of aneurysms which were previously considered poor candidates for coiling more feasible. Significant regional practice variations are likely to influence the proportion of techniques employed to treat aneurysms at different institutions. We describe our experience treating aneurysms at a single, high-volume tertiary care center. Methods: A retrospective review was undertaken of all the aneurysms treated at a single institution (Cleveland Clinic) between 2003 and 2010. Results: 1455 aneurysms were treated at our institution during the study period (45% SAH). Over this period, there was a near-linear increase in the number of aneurysms being treated. 137 were treated in 2003 and 208 were treated in 2010. In 2003, aneurysms were treated equally with clipping (49.6%) and coiling (50.4%). Over the 8-year period, there was a steady decline in the percentage of aneurysms treated surgically. By 2010, 25.5% of aneurysms were treated surgically and 74.5% by endovascular coiling. Among aneurysms that were coiled there has been an increase in the cases that are treated with adjuncts. Balloon-assisted remodeling is currently employed in 57.6% of all coiled aneurysms. The number of stent-assisted cases increased modestly and then has reached a plateau since 2007. Among stent-assisted cases, the "coil-through" technique was initially the preferred method (84% of all stent-assisted cases in 2003–2004). There has been a dramatic decrease in the proportion of "coil-through" cases and currently only 38% of stent-assisted cases are performed employing this method. The "coil-stent" and "jailing" techniques have remained relatively constant over time and both still represent a relative minority in treatment method, currently constituting 11.4% and 13.9%, respectively. The most dramatic increase in the relative proportion of a single method was the more widespread use of 'balloon-stent'. Initially employed in 12% of stent-assisted cases, it is currently employed in 35.4% of cases. Conclusions: Significant changes in practice trends for aneurysm treatment have been observed at a single, high-volume tertiary care center over the past decade. Although these changes are multifactorial, they are explained in party by institutional comfort level with the adoption of adjunctive techniques with a growing number of aneurysms treated with balloon remodeling and the "balloon-stent" technique. A preference of endovascular strategies over microsurgical clipping for treatment of both ruptured and unruptured aneurysms is now evident.